Children’s play paints and cosmetics: a potential source of toxic elements (metals)? - Rebelo, Andreia (2012)
Toxic elements can be found in many products used in the school environment and their presence may present a potential source of hazards for young children. Children´s play paints (finger-paints, gouaches, acrylics, water paints) and decorative cosmetics are commonly used as didactic products in preschool activities. These products composition include a wide range and variety of natural and synthetic substances, such as pigments, solvents, water, preservatives and fragrances, that are directly applied to human skin contributing to a local exposure.